Soil Nitrogen Stock of Primary and Restored Mangrove Forests in Ranong Biosphere Reserve, Thailand - Kitpakornsanti, Kittiwan; Pengthamkeerati, Patthra; Worachananant, Pasinee; Limsakul, Atsamon (Journal of Fisheries and Environment, 2022)
Mangrove forests play an important role in nutrient cycling, particularly due to their high rates of nitrogen enrichment. However, few studies have investigated the soil nitrogen stock in mangrove forests. This study was conducted at mangrove sites in the Ranong Biosphere Reserve in Thailand that represented three different conditions: primary, reforested, and natural regeneration. The soil nitrogen stock was estimated at four depth layers (0-10, 10.1-15, 15.1-30 and 30.1-50 cm). The results showed that the primary mangrove site had significantly higher soil nitrogen stock (mean ± standard deviation; 10.38±1.29 t N·ha-1) due to the greater time for nitrogen accumulation in the soil, followed by the reforested site (6.02±0.69 t N·ha-1) and the natural regeneration site (5.16±0.37 t N·ha-1). The soil nitrogen content was highest in the surface soil (0-10 cm) and gradually decreased with increasing depth. Nitrogen accumulation rates were significantly higher for the primary mangrove site (8.16±0.39 g N·m-2·year-1), followed by the reforested site (2.56±0.07 g N·m-2·year-1) and the natural regeneration site (1.07±0.07 g N·m-2·year-1). Soil texture (clay and silt), bulk density, and total nitrogen content were significantly correlated to total nitrogen stock. These results demonstrate that conservation and restoration programs for mangrove forests are effective practices that help ensure this vital ecosystem continues to function as a long-term nitrogen sink and nitrogen cycling site for the coastal system as a whole.